2012
DOI: 10.3747/pdi.2012.00046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing of Dialysis Commencement on Clinical Outcomes of Patients with Planned Initiation of Peritoneal Dialysis in the Ideal Trial

Abstract: ORIGINAL ARTICLES♦ Background: Since the mid-1990s, early dialysis initiation has dramatically increased in many countries. The Initiating Dialysis Early and Late (IDEAL) study demonstrated that, compared with late initiation, planned early initiation of dialysis was associated with comparable clinical outcomes and increased health care costs. Because residual renal function is a key determinant of outcome and is better preserved with peritoneal dialysis (PD), the present prespecified subgroup analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…It was once considered that the earlier dialysis was started, the better the life condition and expectancy achieved. However, a single randomized controlled trial, the Initiating Dialysis Early and Late (IDEAL) study, demonstrated that earlier dialysis initiation (at an estimated creatinine clearance of 10-14 ml/ min) did not reduce mortality compared to later initiation (estimated creatinine clearance of 5-7 ml/min) [57] . Therefore, it cannot be predicted exactly when it is best to initiate dialysis with regard to the rate of decline in RRF.…”
Section: Time Of Initiating Dialysismentioning
confidence: 99%
“…It was once considered that the earlier dialysis was started, the better the life condition and expectancy achieved. However, a single randomized controlled trial, the Initiating Dialysis Early and Late (IDEAL) study, demonstrated that earlier dialysis initiation (at an estimated creatinine clearance of 10-14 ml/ min) did not reduce mortality compared to later initiation (estimated creatinine clearance of 5-7 ml/min) [57] . Therefore, it cannot be predicted exactly when it is best to initiate dialysis with regard to the rate of decline in RRF.…”
Section: Time Of Initiating Dialysismentioning
confidence: 99%
“…19 We identified two studies that reported quality of life, six that reported hospital admissions and one that described nutritional status as measured by total body nitrogen. Following the completion of our review, we identified two secondary analyses of the IDEAL study that reported echocardiographic findings and selection of peritoneal dialysis; 21,22 these outcomes were not relevant to this guideline and were not considered further. Details and key findings of these studies are summarized in Appendix 1.…”
mentioning
confidence: 99%
“…Such fracturing was demonstrated in the IDEAL study (1), in which patients who were randomized to start PD later in the course of their chronic kidney disease (5 -7 mL/min) were less likely to actually be established on PD therapy (they were more likely to receive hemodialysis) than were those who were randomized to start PD earlier (10 -14 mL/min).…”
Section: Editor's Introduction High-quality Patient Care Pathways Arementioning
confidence: 92%